Prevalence of Diabetes and Hypertension among Pregnant Women Attending Medical Laboratories in Zawia City, Libya - Marwa Al mabrok,; Al Basher Ashour,; Hebah Zahmoul,; Asadig Alghoull,; Reema Albaseer, (AlQalam Journal of Medical and Applied Sciences, 2026)
This study aimed to identify and evaluate the prevalence of diabetes and blood pressure among a sample of 230 pregnant women, classified according to the number of pregnancies and different age groups, in the city of Zawiya, western Libya, from January 2025 to March of the same year. The study reached several findings, including the prevalence of diabetes and high blood pressure among a group of pregnant women by age group and the number of pregnancies per woman. The age group from (24-29) recorded the highest rate of diabetes, reaching 13.48%, followed by the age group from (18-23), and the age group from (30-35) with 7.39% for both, while the age group from (36-41) recorded the lowest rate of diabetes, reaching 5.65% As well as the rate of high blood pressure in women, the highest percentage was recorded in the age group (24-29) at 7.82%, followed by the age group (30-35) at 7.34% of the total cases, and the age group (36-41) recorded the lowest percentage at 5.22%. This is consistent with many studies that have addressed the subject in different regions of the world. In addition to the number of pregnancies in women, the highest rate of diabetes and high blood pressure was recorded in the first pregnancy at 10.43% of the number of pregnancies among pregnant women. The rate of diabetes and high blood pressure by age group for all pregnant women in the study sample was recorded at 35.21% and 27.82%, while the rate of diabetes due to the number of pregnancies among all pregnant women was 40.87%, and the rate of high blood pressure was recorded at 33.91% among the study sample. The incidence of diabetes and high blood pressure varied among pregnant women, and the number of pregnancies varied in terms of rates. This may be due to many other variables that affect the incidence of diabetes and high blood pressure during pregnancy, the number of pregnancies, and other factors. The study recommended conducting various scientific studies and research that address this aspect of the lives of pregnant women who need great care and attention, including early screening Periodic follow-up of cases, and provision of high-precision health and therapeutic services to enhance the health of pregnant women